High toughness fully physical cross-linked double network organohydrogels for strain sensors with anti-freezing and anti-fatigue properties. Issue 20 (20th September 2021) - Tang, Li; Wu, Shaoji; Xu, Yue; Cui, Ting; Li, Yuhua; Wang, Wu; Gong, Liang; Tang, Jianxin
Abstract : A novel, high toughness, double network organohydrogel was fabricated with fast self-recovery, anti-freezing and anti-fatigue properties and high sensing performance. Abstract : Flexible sensors based on conductive hydrogels have been of wide interest in the field of smart wearable electronics due to the excellent stretchability and strain-responsive ability. However, lacking harsh environment tolerance and self-recovery properties seriously limit their practical applications. Therefore, the development of anti-fatigue hydrogels with anti-freezing and water-retaining abilities is urgently required. In this study, we constructed a fully physically cross-linked gelatin/poly( N -hydroxyethyl acrylamide)/glycerin/lithium chloride double network (gelatin/pHEAA/Gly/LiCl DN) organohydrogel based on a hydrogen bond crosslinking strategy using a facial one-pot method. The dynamic hydrogen bond in the DN organohydrogels provided an effective energy dissipation pathway, which produced gels with high tensile strength/strain (2.14 MPa/1637.49%), fast self-recovery properties and strong interfacial toughness. The introduction of binary solvents of water and glycerin endowed the DN organohydrogels with excellent anti-freezing and water-retaining properties. Furthermore, a simple flexible sensor was fabricated based on the organohydrogel for detecting human motions. The sensor not only showed remarkable sensitivity (GF = 14.54), broad strain range (0–1600%) and high response speed (0.2 s), but also presented accurate and reliable signals under different mechanical deformations and low temperature (−20 °C). This work provides a feasible way to build high mechanical and sensing performance organohydrogel-based sensors with anti-freezing and water-retaining abilities, which greatly promotes the application of flexible sensors in the field of smart wearable electronic devices, electronic skin and human/machine interface.